Hubungan Tingkat Stres Akibat Kerja Dengan Tingkat Kepuasan Kerja Pada Perawat RSUD Dr. Moewardi Di Surakarta - Saptorini, Iin Aprillia Dwi (2016)
Hospitals in the United States noted the average 6.8 injury or injury associated with a job and disease for every 100 employees full in 2011, it is nearly doubled to private industry overall. Job satisfaction can improve durability individuals to stress and impacts of stress and on the other hand, a stress that perceived by individual can be a source of discontent. To know level Stress by Job relations with the level of work satisfaction nurses in RSUD Dr. Moewardi Surakarta. The kind of research this is research observational with the approach cross sectional. The entire population research nurse at the emergency room , HCU , ICU , and orchids hospital Dr. Moewardi Surakarta about 142 nurse. The sample of the in research about 60 respondents, the sample collection Proportionate Stratified Random Sampling. The correlation used in this research using test the Spearman Rank (Rho). The results of the study a significant relation exists between the level of stressor with the level of satisfaction work (pvalue=0,000) the value a correlation coefficient ( r = -0,636) with a level of closeness that (r) strong where the value of from 0,60-0,799 (strong). Advice for this research is needed further research by doing research relating to level stressor relations with the satisfaction work at the hospital patients.